Effects of thrombin and its related peptide fragments on neutrophils - Lim, Chun Hwee (2018)
Wounds are highly proteolytic environments containing proteases from host cells as well as colonising bacteria. In this milieu, novel host defence peptides derived from host proteins such as cytokines and coagulation pathway proteins are being generated. For example, proteolysis of the serum protein thrombin forms C-terminal peptides that have antibacterial and anti-endotoxic properties. In addition, these peptides were shown to have immunomodulatory effects on monocytes, but whether they have any effects on the other major innate immune cells, neutrophils, was not known. Hence, we aimed to address the immunomodulatory potential of these C-terminal truncations on neutrophil functions. We show that the prototypic thrombin C-terminal peptide GKY25 can attenuate neutrophil responses to lipopolysaccharides (LPS) and the cytokine interleukin-8 in vitro. Independently, GKY25 induced the shedding of neutrophil adhesion molecule CD62L, thus reducing neutrophil surface tethering capacity in vitro. Furthermore, subcutaneous or intraperitoneal GKY25 reduced neutrophil response to subcutaneous LPS administration in vivo. This demonstrates the therapeutic potential of GKY25 in modulating host response in endotoxin-mediated conditions. Of interest was to investigate whether endogenous C-terminal peptides can also modulate neutrophils’ activities. Using two C-terminal truncated peptides – HVF18 and FYT21 – generated by the proteolysis of thrombin by neutrophil and Pseudomonas aeruginosa elastases respectively, we show that FYT21 was more effective at inhibiting LPS-induced neutrophil response at physiologically relevant concentrations. Furthermore, FYT21, even more effectively than GKY25, reduced neutrophil surface CD62L. These indicate a possible host evasion mechanism where FYT21 reduces inflammatory responses to facilitate P. aeruginosa colonisation. Neutrophils’ presence in wounds extend beyond their inflammatory functions; they produce neutrophil extracellular traps (NETs), an extracellular network of DNA decorated with neutrophil-derived proteins. NET-associated proteins have been argued to trap and kill bacteria, as well as being implicated in autoimmune complications. However, in vitro assessments of its proteome (or NETome) had excluded external factors’ influence and non-neutrophil proteins from analyses. Using a reductionistic approach, we applied physiological concentrations of thrombin and plasmin, two of the more abundant serum proteins representing the different stages of wounding, to NETs. Using a proteomic approach, we identified 164 NET-associated proteins, where majority of the proteins were shared between treatments but were different in abundances. We show that most classical NET-proteins were reduced in the presence of thrombin and plasmin, possibly through direct proteolytic effects (i.e. on histones) or other regulatory mechanism (i.e. for neutrophil elastase). This indicates that the NETome, under various inflammatory conditions, can be dynamically different. We propose that by elucidating these differences in a physiological context, it could potentially lead to discovery of novel diagnostic or therapeutic markers relevant to specific diseases where NETs are implicated.